2018
DOI: 10.1590/s1679-87592018017406603
|View full text |Cite
|
Sign up to set email alerts
|

Tidal and subtidal oscillations in a shallow water system in southern Brazil

Abstract: Andrade et al.: Sea level oscillations in shallow waters 245 Tidal and subtidal oscillations in a shallow water system in southern Brazil Sea level oscillations in time scales between hours and days have a great vertical amplitude regarding the low lying coastal gradient of the beaches in the Rio Grande do Sul coast. However, the mechanism of oscillations is poorly understood since the scarcity of observational data makes it impossible to determine the forces that control sea level oscillations. Therefore, hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…In addition to gravitational motion of the sun, the moon, and the earth, meteorology effects such as atmospheric pressure and wind power also contribute to the tide level (Andrade et al 2018;Truccolo et al 2006). Other contributing factors include the shape of the beach, coastline, and coastline depth (Kleinhans et al 2017;Marone et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to gravitational motion of the sun, the moon, and the earth, meteorology effects such as atmospheric pressure and wind power also contribute to the tide level (Andrade et al 2018;Truccolo et al 2006). Other contributing factors include the shape of the beach, coastline, and coastline depth (Kleinhans et al 2017;Marone et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that the studies on the tidal changes from the area near the equator are few. Here, we will only focus on gravitational effects, while the meteorological effects, in general, cannot be ignored (Andrade et al 2018;Pugh 1996;Truccolo et al 2006). It is shown that the tide levels are dominated Tide level in time and frequency domains... by four major gravitational constituents from the sun and the moon (M2, S2, K1, O1) and tide level dynamics is replicated well by the Lorentz-type resonance (Wooten 1972).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tide is semidiurnal, with an average range of about 0.5 m. Storm surges are frequent and can raise the water level by more than 1 m [45]. Based on a 30-year (1979 and 2008) deep-water wave modeling with the NOAA WAVEWATCH III®, the average wave directions are from south quadrant (~51%, the sum of annual occurrence), followed in order of importance by east quadrant (~43%, the sum of annual occurrence).…”
Section: Oceanographic Settingmentioning
confidence: 99%
“…As marés ao longo da costa oceânica do Rio Grande do Sul são semidiurnas com amplitude de micro--maré (<50 cm). Forçantes meteorológicas e oscilações em frequência submareal podem sobrelevar o nível d'água em mais de 66 cm (ANDRADE et al, 2018). Com base em dados de campo e em modelagem numérica, as direções de onda predominantes na plataforma ROSA et al, 2017).…”
Section: Aspectos Oceanográfi Cos E Climáticosunclassified